Key determinants of customer satisfaction: evidence from Malaysia grocery stores - Mohammed, Al-Ali (Asian Research Publishing Network (ARPN), 2015)
Customer satisfaction is critical to retail success. Concentrating on customer satisfaction has become a major goal in retailing industry, especially in grocery retail. This work examines the key determinants of customer satisfaction in grocery retailing and measure the link between store attributes and customer satisfaction. In addition, it aims to find out the effect size of these determinants on overall customer satisfaction in an emerging market, namely Malaysia. For this purpose, an extensive dataset from 313 shoppers who had carried out their purchase in different type of grocery stores has been analyzed. Using Partial Least Squares-SEM (PLS-SEM) analysis method, we show that three determinants (‘‘monetary value’’, ‘‘service and convenience’’, and ‘‘store quality image’’) have a direct impact on customer satisfaction. However, the weight that each factor shows is different. Results may help managers of grocery stores in Malaysia to develop and implement more successful relationship marketing strategies.